Adobo ni Juan Restaurant a feasibility study on setting up an adobo restaurant - Bartolome, Carlo; Bautista, Hazel Ann; Reinoso, Eric John; Torres, Jillian Marie
A study was conducted to determine the feasibility of setting up an Adobo restaurant. It was named Adobo ni Juan Restaurant, and its feasibility with respect to four aspects were studied, namely marketing, technical, financial, and socio profitability analysis under a 5-year time horizon. The marketing feasibility section discussed Adobo ni Juan's target market - students and professionals belonging in the socioeconomic classes C and D. Furthermore, to market the restaurant, promotions and advertising will be done and the marketing expenses were estimated to be PhP 346,308, whereas the revenue was projected to be Php 14,882,439.27. The marketing expenses make up 2.33% of the projected revenues. The technical feasibility section discussed the requirements needed in setting-up Adobo ni Juan Restaurant - material requirements, equipment and tooling, capacity planning, service labor needs, production planning, and facilities design. A cost analysis was performed to estimate the amount needed to pay for these requirements. Costs involved were both paid one-time and/or on a monthly basis. The technical expenses required were estimated to be PhP 11,460,412.23, 77.01% of the revenues projected from the marketing feasibility. The financial feasibility section discussed how to estimate total investment and used financial statements to determine how funds are generated and spent. A total investment cost of PhP 1,000,000 will be needed, the half to be shouldered by the sole proprietor of Adobo ni Juan Restaurant and the remaining half to be loaned from Standard Chartered Bank at 1.38% monthly payable within 48 months. The last section was concerned with the social profitability, or how Adobo ni Juan Restaurant can make a positive impact to the community or with the government. Quantitatively, it was found that operating a restaurant can contribute to the government by paying its taxes and having its employees also pay taxes. Qualitatively, the Filipino motif displayed in Adobo ni Juan Restaurant can foster good relations by showcasing Filipino culture diversity.